The pivotal role of EMT-related noncoding RNAs regulatory axes in hepatocellular carcinoma - Ghionescu, Alina-Veronica; Sorop, Andrei; Dima, Simona Olimpia (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) remains a major health problem worldwide, being the leading cause of cancer-related deaths, with limited treatment options, especially in its advanced stages. Tumor resistance is closely associated with the activation of the EMT phenomenon and its reversal, being modulated by different molecules, including noncoding RNAs (ncRNAs). Noncoding RNAs have the potential to function as both tumor suppressors and oncogenic molecules, controlling the malignant potential of HCC cells. Basically, these molecules circulate in the tumor microenvironment, encapsulated in exosomes. Their impact on cell biology is more significant than originally expected, which makes related research rather complex. The temporal and spatial expression patterns, precise roles and mechanisms of specific ncRNAs encapsulated in exosomes remain primarily unknown in different stages of the disease. This review aims to highlight the recent advances in ncRNAs related to EMT and classifies the described mechanism as direct and indirect, for a better summarization. Moreover, we provide an overview of current research on the role of ncRNAs in several drug resistance-related pathways, including the emergence of resistance to sorafenib, doxorubicin, cisplatin and paclitaxel therapy. Nevertheless, we comprehensively discuss the underlying regulatory mechanisms of exosomal ncRNAs in EMT-HCC via intercellular communication pathways.